The New Opera : how can the modern opera reach new audience? - Alexandra Chernyshova 1979- (2023)
This research paper builds on the concept „The New Opera“ and aims to identify new ways and strategies that will connect new audiences with Opera houses today. The theoretical value of the study is to identify the New Opera concept and bringing new audiences to the Opera based on the theories of Griswold ́s and Drucker's. The study used semi-structured qualitative interviews with Opera specialists in Europe, the USA and Iceland. This involved Opera singers, directors, producers, critics, and scholars who were selected based on their extensive experience and knowledge in the field. Thematic analysis revealed that many people highly appreciate Opera for its combination of music and theatre, sense of anticipation before a performance begins, vivid spectacle, complexity in composition, and live performances. The analysis also identified various problems related to the success of the Opera form, such as lack of creativity or freedom within production due to staleness that lead individuals away from attending performances. The study found out that more innovation is needed for the Opera to remain relevant and able to attract new audiences. It is also found out that this can only be achieved through a collective effort of all individuals involved in this art form, i.e. those performing, those staging, and the opera administration on by and large. It is also showed that the New Opera should rely more on effective promotional strategies like social media campaigns along with word-of-mouth marketing. Key words: new opera, innovation, new audiences, creativity, new strategies. Ritgerðin er lokuð tímabundið að ósk höfundar